Phenotypic, morphometric characterization and population structure of Pasundan cattle at West Java, Indonesia - SYAHRUDDIN SAID; WIDYA PINTAKA BAYU PUTRA; SAIFUL ANWAR; PASKAH PARTOGI AGUNG; HANI YUHANI (Society for Indonesian Biodiversity, 2017)
Said S, Putra WPB, Anwar S, Agung PP, Yuhani H. 2017. Phenotypic, morphometric characterization and population structure of Pasundan cattle at West Java, Indonesia. Biodiversitas 18: 1638-1645. Identification of phenotypic and morphometric characteristics in indigenous cattle is important in characterizing breeds of animals. This study was carried out to identify the phenotypic and morphometric characteristics of 813 indigenous Pasundan cattle from West Java Province of Indonesia. The coat color of Pasundan cattle is mainly solid reddish brown (>90%) with black color on hoof (>90%), switch of tail (>80%), eyelid (>90%), muzzle (>90%), horn (>90%) and whitish color on mouth lash (>80%) and reddish brown color on legs (>60%) and rump patch (>60%). The physical characteristic of Pasundan cattle mainly is the hump in males (65.23%) or humpless in female (74.91%), small dewlap size (>60%), presence of back line (>60%) and horned (>80%) with upper curved horn (>90%). The average of withers height (WH), body length (BL), chest girth (CG) and scrotal circumference (SC) of adult male Pasundan cattle were 128.94+16.69 cm; 128.72+15.98 cm; 159.36+15.84 cm and 17.68+3.51cm respectively. Therefore, the average of WH, BL, and CG of adult female Pasundan cattle was 122.56+11.40 cm; 115.63+19.06 cm and 140.13+12.16 cm respectively. Natural Increase (NI) and calf crop values were 18.46% (low category) and 20.40% respectively. Net Replacement Rate (NRR) values were 300% (male) and 507% (female) and indicated that West Java province was still capable to produce seed stock per year.